Cross-Cultural Indonesia-Malaysia for Strengthening Learning Products to Achieve Sustainable Goals - Firmansyah Firmansyah; Asnarni Lubis; Noorjima Abdul Wahab; Ayu Utami Br. Simbolon (LPPI UMN AL WASHLIYAH, 2025)
This community service activity was carried out based on an international collaboration between Indonesia and Malaysia. Indonesia was represented by Universitas Muslim Nusantara Al-Washliyah (UMN Al-Washliyah), while Malaysia was represented by Universiti Sultan Zainal Abidin (UniSZA). The main focus of the program was cultural exchange as a unique foundation for creating Project-Based Learning approaches. The implementation method involved a Knowledge Transfer Programme, with UniSZA students as the primary partners. The results reveal that integrating Malay culture from both Indonesia and Malaysia strengthens cross-national educational values and significantly contributes to achieving Sustainable Development Goals (SDG) point 4, which emphasizes quality education. The empowerment of cultural identity within the educational context serves as a strategic instrument to enhance students' understanding, tolerance, and global competence.